Cardioprotection of Repeated Remote Ischemic Conditioning in Patients With ST-Segment Elevation Myocardial Infarction - Chen, Shaomin; Li, Shijia; Feng, Xinheng; Wang, Guisong (Frontiers in Cardiovascular Medicine, 2022)
Background: Repeated remote ischemic conditioning (RIC) after myocardial infarction (MI) has been shown to improve left ventricular (LV) remodeling in experimental studies, but its cardioprotective effect in ST-segment elevation myocardial infarction (STEMI) patients is still unknown. Objective: To investigate whether repeated RIC started early after primary percutaneous coronary intervention (PCI) can improve LV function in STEMI patients. Methods: STEMI patients treated by primary PCI were included and randomised to the repeated RIC group (n=30) or the control group (n=30). RIC was started within 24 hours after PCI and repeated daily for 1 week, using an Auto RIC device. 3D speckle-tracking echocardiograohy (STE) was used to assessed LV function. The primary study endpoint was the change in LV global longitudinal strain (GLS) from baseline to 1 month after PCI. Results: The repeated RIC group and the control group were well matched at baseline including mean GLS (-9.8±2.6% vs -10.1±2.5%，P=0.62). Despite there was no significant difference in mean GLS at 1 month between the two groups(-11.9%±2.1% vs -10.9%±2.7%，P=0.13), the mean change in GLS from baseline to 1 month was significantly higher in the treatment group than in the control group (-2.1%±2.5% vs -0.8%±2.3%，P=0.04). There were no significant differences in the changes in global circumferential strain (GCS), global area strain (GAS), global radial strain (GRS), LV ejection fraction (LVEF), LV end-diastolic volume (LVEDV) and LV end-systolic volume (LVESV) between the two groups. Peak creatine kinase isoenzyme-MB, peak high-sensitivity troponin T and plasma N-terminal pro brain natriuretic peptide (NT-proBNP) levels at 24 hours after PCI did not differ significantly between the two groups, but NT-proBNP levels at 1 week were significantly lower in the treatment group than in the control group [357.5 (184.8～762.8) vs 465.0 (305.8～1525.8) pg/ml，P=0.04]. Conclusion: Daily repeated RIC started within 24 hours after PCI can improve GLS and reduce plasma NT proBNP level in STEMI patients.